2012
DOI: 10.1088/1367-2630/14/6/063001
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective couplings in x-ray-detected magnetic resonance spectra of rare-earth-substituted yttrium iron garnets

Abstract: Site-selective x-ray detected magnetic resonance (XDMR) spectra were recorded in transverse detection geometry on two iron garnet thin films grown by liquid phase epitaxy (LPE) on oriented gadolinium gallium garnet (GGG) substrates: whereas the stoichiometry of the first film corresponded to pure yttrium iron garnet (1 = YIG) used as reference, yttrium was partly substituted with lanthanum and lutetium in the second film (2 = La-Lu-YIG). Surprisingly, the XDMR spectra of film 2 recorded at either the Fe K-edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Each unit cell consists of 12 trivalent Fe atoms that are tetrahedrally coordinated with oxygen atoms (d sites, point group S 4 ), 8 Fe atoms that are octahedrally coordinated (a sites, point group S 6 ), and 12 dodecahedrally coordinated Gd atoms (c sites). The two Fe sub-lattices are strongly coupled via antiferromagnetic superexchange (exchange constant J ad 32 cm −1 ), [27] with a Néel temperature of about T N = 550 K. Since the Gd moments are more weakly exchange coupled to the Fe a sub-lattices (J ac 7 cm −1 ) [27] leading to an ordering temperature of the Gd spins at around 69 K, [28] they experience an effective magnetic field below T N and can be treated as an 'exchange-enhanced' paramagnetic moment. [29] As a consequence the Gd magnetization can be described by a strongly temperature-dependent Brillouin function for spin 7/2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Each unit cell consists of 12 trivalent Fe atoms that are tetrahedrally coordinated with oxygen atoms (d sites, point group S 4 ), 8 Fe atoms that are octahedrally coordinated (a sites, point group S 6 ), and 12 dodecahedrally coordinated Gd atoms (c sites). The two Fe sub-lattices are strongly coupled via antiferromagnetic superexchange (exchange constant J ad 32 cm −1 ), [27] with a Néel temperature of about T N = 550 K. Since the Gd moments are more weakly exchange coupled to the Fe a sub-lattices (J ac 7 cm −1 ) [27] leading to an ordering temperature of the Gd spins at around 69 K, [28] they experience an effective magnetic field below T N and can be treated as an 'exchange-enhanced' paramagnetic moment. [29] As a consequence the Gd magnetization can be described by a strongly temperature-dependent Brillouin function for spin 7/2.…”
mentioning
confidence: 99%
“…In other words, the magnons in the Fe sub-lattices will substantially contribute to the SSE for T < T C ≈ 550 K, while the Gd sub-lattice exhibits a qualitatively different thermomagnetic behavior and significantly contributes to the SSE only for T T Gd ≈ 65 − 85 K. As mentioned above, the latter temperature is often also referred to as the Gd ordering temperature in the literature. [28] This assumption is motivated by the existing literature investigating finite temperature effects on ferromagnets via the self consistent renormalization of magnon dispersions. [33] In particular, it has been shown that the magnons cease to be the admissible eigenstates above a temperature around the ordering temperature.…”
mentioning
confidence: 99%